The effects of geometrical parameters on resonance frequency of Inverted Split Ring Resonators (ISRRs) - Ismail YARIÇI; Yavuz ÖZTÜRK (International Journal of Applied Methods in Electronics and Computers, 2021)
In this study, an inverted split ring resonator (ISRR) was designed and the effects of the design geometrical parameters on the resonance frequency presented by using an equivalent circuit approach. The width of the rings, w, the width of ring split, s, and the outer length of the resonator, lres were chosen as geometrical parameters. The determined designs were implemented by making simulations with electromagnetic design software, and the numerically obtained results were compared with theoretically obtained results. A good agreement of simulation and theoretical results was achieved and presented.